Eklezja Mateusza – eschatologiczną „Resztą Izraela”? - Żywica, Zdzisław (Collectanea Theologica, 2016)
In a holistic look at the history of Israel and the Church, Evangelist Matthew seems to express the hope that taken by him idea of “Rest”, proves to be a kind of bridge for the followers of rabbinic Judaism. He also trusts that in the eschatological times – finally closed by the Second Coming of the Son of Man – they profess, at least some of them, faith in Jesus from Nazareth as the Messiah and Son of God at the same time. Faith confessed by them will allow to enter into the Church and obtain the same equal rights as other participants of that idea in the following centuries of the God’s salvation history, in which the chosen people of Abraham will be able to participate as the only nation from the beginning until the definite its completion, with only a short break discontinued, however, by conversion and return to God Yahweh – the Father of Jesus.